PRODUKTIVITAS TENAGA KERJA DAN TINGKAT INFLASI DI INDONESIA - ikhma ramadhani; Doni Satria (Universitas Negeri Padang, 2026)
This study aims to analyze the effect of inflation on labor productivity in Indonesia by incorporating education, health, and information and communication technology (ICT) as control variables. The study uses panel data from 34 provinces in Indonesia during the period 2015–2024, resulting in 340 observations. The analytical method employed is the System Generalized Method of Moments (System GMM) to address endogeneity issues and capture the dynamic nature of labor productivity. The results show that inflation has a positive and statistically significant effect on labor productivity, with a short-run coefficient of 0.1117 and a long-run coefficient of 0.1668. In addition, education and health have positive and significant effects, while ICT has a negative and significant effect on labor productivity. These findings indicate that moderate inflation can stimulate economic activity and increase productivity, while human capital plays a crucial role in enhancing labor productivity. However, the negative impact of ICT suggests that technology utilization has not been fully optimized for productive activities. This study contributes to the literature by providing empirical evidence using a dynamic panel approach at the provincial level in Indonesia. The findings imply that maintaining stable and moderate inflation, along with improving human capital and optimizing technology utilization, is essential to enhance labor productivity.